Damage Source Identification of Reinforced Concrete Structure Using Acoustic Emission Technique - Panjsetooni, Alireza; Muhamad Bunnori, Norazura; Vakili, Amir Hossein (Hindawi Publishing Corporation, 2013)
Acoustic emission (AE) technique is one of the nondestructive evaluation (NDE) techniques that have been considered as the prime candidate for structural health and damagemonitoring in loaded structures. This technique was employed for investigation process of damage in reinforced concrete (RC) frame specimens. A number of reinforced concrete RC frames were tested under loading cycle and were simultaneously monitored using AE.The AE test data were analyzed using the AE source location analysis method. The results showed that AE technique is suitable to identify the sources location of damage in RC structures.